A short guide to writing about art - Barnet, Sylvan (Boston : Pearson, 2015)
This book is intended for art courses where there is a writing component. This text guides art students through the writing process. Students are shown how to analyze pictures (drawings, paintings, photographs), sculptures and architecture. The text includes: coverage of essential writing assignments including formal analysis, comparison, research paper, review of an exhibition, essay examination; clear step-by-step writing instructions guiding students though the research and writing processes; sample essays, with analytic comments by the author, demonstrating the virtues of effective writing.
Writing about art -- Writing about art : the big picture -- Formal analysis and style -- Analytic thinking -- Writing a comparison -- Writing an entry in an exhibition catalog -- Writing a review of an exhibition -- Virtual exhibitions : writing text panels and other materials -- How to write an effective essay -- Style in writing -- Art-historical research -- Some critical approaches -- Writing a research paper -- Manuscript form -- Writing essay examinations -- Symbols commonly used in annotating papers -- Brief guide to instructions in writing -- Frequently asked questions
Includes bibliographical references and index
Keywords: Art criticism -- Authorship